Pelaksanaan Peralihan Hak Milik Atas Tanah yang Tidak Dibuat di Hadapan PPAT: (Studi Putusan Nomor 116/Pdt.G/2021/Pn Prp) - Dimas Harry Agustino; Hasim Purba; Tony (Jurnal Hukum Lex Generalis, 2025)
This research examines the transfer of land rights which should be conducted in accordance with Government Regulation No. 24 of 1997 and Government Regulation No. 37 of 1998 through PPAT deeds, however in practice there are still many land sale and purchase transactions that do not comply with existing statutory provisions. Using normative juridical method with descriptive analytical approach and secondary data sources through library research, this study found that court decisions can serve as the basis for land ownership transfer without PPAT deeds and provide legal certainty because they have the same evidentiary strength as authentic deeds, and in decision No. 116/Pdt.G/2021/PN Prp, the judge granted Suliyanto's lawsuit with the consideration that the land was controlled and managed by the plaintiff without objection from any party, thus ordering the transfer of certificate title from Enjum to the plaintiff at the National Land Agency Office of Rokan Hulu Regency.